ANALISIS PROFIL KETERAMPILAN BERPIKIR KRITIS KONSEP SAINS MAHASISWA PGSD - Elyas Djufri; Devi Septiani; Ahmad Syauqi Hidayatullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This study aims to analyze the profile of critical thinking skills of PGSD students in learning science concepts. Critical thinking indicators used as a reference in observing critical thinking in this study include: analyzing, predicting, designing ideas. The research carried out includes the type of quantitative research with a descriptive approach. where the data were analyzed by calculating the cognitive ability score with a scoring technique with corrections to guess answers. The research subjects for the third semester students of PGSD UST Yogyakarta are 80 students for the 2021/2022 academic year. The results showed that the critical thinking skills of PGSD students from grades A and B had critical thinking skills with an average (medium) scale of 23.75%, then critical thinking abilities with low criteria of 33.75%. Furthermore, students who have very high critical thinking skills are 6.25%. While those with very low criteria are only 36.25%.